Corporate performance management best practices : a case study approach to accelerating CPM results - Paladino, Bob, 1959- (Hoboken, N.J. : Wiley, 2013)
Business improvement best practices and a proven methodology for improving corporate performance management, illustrated through a high performing program including numerous team case studies Corporate performance management consists of a set of processes that help organizations optimize their business performance. It provides a framework for organizing, automating and analyzing business methodologies, metrics, processes and systems that drive business performance. Corporate Performance Management Best Practices will help your organization benchmark itself against the best.
Preface Acknowledgments Chapter 1 Introduction Corporate Performance Management Best Practices Executive Views on CPM MidMichigan Awards, Honors, and Results My Promise Notes Chapter 2 Corporate Performance Management Core Best Practices Principle 1: Establish and Deploy a CPM Office and Officer Principle 2: Refresh and Communicate Strategy Principle 3: Cascade and Manage Strategy Principle 4: Improve Performance Principle 5: Manage and Leverage Knowledge CPM Maturity Model and Best Practice Pentagon Scoring Diagnostic Note Chapter 3 Corporate Performance Management at MidMichigan Health Strategic Context and CPM Approach MidMichigan Health CPM Program Overview and Journey Principle 4: Improve Performance "10 Step Business Improvement Approach" Principle 4: Improve Performance "10 Step Business Improvement Approach" Steering Committee Notes Chapter 4 Principle 4 Improve Performance -- The MidMichigan Health System Journey CPM Maturity Levels for Principle 4 Improve Performance Summary Note Chapter 5 Improve Performance Best Practices Core Best Practices 35 New Best Practices Summary Notes Chapter 6 Shared Services 10 Step Team Best Practice Cases Finance: Accounts Payable and Disbursements 10 Step Team Case Study, Smart Spending Finance: Financial and Management Reporting 10 Step Team Case Study, Streamline Information Human Resources: New Employee Requisition 10 Step Team Case Study, Simplify Hiring Supply Chain Management: New Product Requisition 10 Step Case Study, Manage Innovation Notes Chapter 7 Support Units: 10 Step Team Best Practice Cases Laboratory Services 10 Step Case Study, Optimize the System Pharmacy Services 10 Step Team Best Practice Case, Smarter Formularies Notes Chapter 8 Core and Specialty Businesses 10 Step Best Practice Cases Emergency Department: 10 Step Team Best Practice Cases, Improve Throughput, Customer Scores and Revenue Care Coordination ...
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Organizational effectiveness -- Case studies; Performance -- Management -- Case studies; Management -- Case studies; Health care reform -- Case studies; BUSINESS & ECONOMICS -- Quality Control; BUSINESS & ECONOMICS -- Total Quality Management; Health care reform; Health care reform -- Case studies; Management; Management -- Case studies; Organizational effectiveness; Organizational effectiveness -- Case studies; Performance - Management; Performance -- Management -- Case studies; Performance -- Management; Health care reform; Management; Organizational effectiveness; Performance -- Management; Electronic books; Electronic books; Electronic books; Case studies